FAMILY DYNAMICS AND ITS INFLUENCE ON RELIGIOUS EDUCATION AMONG QURAN AND TAFSIRI STUDENTS OF UIN SUMATERA UTARA - Rizki Ananda Pratama Barutu; M. Taufiq (Al - Mujaddid: Jurnal Ilmu-ilmu Agama, 2023)
Abstrack This study investigates the impact of family dynamics on the religious education of students in the Quranic Sciences and Tafsir program at UIN Sumatera Utara (UINSU). Using a quantitative survey method, data were collected from 150 students to explore the relationship between family dynamics such as parenting style, family harmony, and parental support and students' academic performance in religious studies. The findings reveal a positive correlation between supportive family environments and higher academic achievement, with students from harmonious families demonstrating stronger religious commitment and better academic results. Conversely, students from conflict-ridden families exhibited lower religious engagement and academic performance. These results underscore the critical role of family dynamics in shaping both the religious understanding and academic success of students in religious studies. The study contributes to the existing literature by emphasizing the need for parental involvement in religious education and suggests further exploration into support mechanisms for students from less supportive family backgrounds.